4. Assessment of mobility and related factors among older patients with osteoporosis - Luc, Tran Viet; Huong, Nguyen Thi Thu; Anh, Nguyen Trung (Tạp chí Nghiên cứu Y học, 2024)
This cross-sectional study was conducted to assess mobility and related factors among older people with osteoporosis treated at the National Geriatric Hospital. Mobility was assessed using the Time Up and Go test (TUG test). The proportion of participants with mobility impairment was 22.0%. The mean time of the TUG test was 12.3 ± 3.9 (seconds). There were significant associations between impaired mobility and age ≥ 80 years old with OR=3.3, knee osteoarthritis with OR=3.5, and diabetes with OR=3.0. There were significant associations between impaired mobility and geriatric syndromes: frailty syndromes (OR=3.5), low levels of physical activity (OR=3.5), and high risk of falls (OR=3.0). In conclusion: one in five older osteoporosis patients has impaired mobility. Our results highlighted that advanced age, knee osteoarthritis, diabetes, and geriatric syndromes such as frailty, low physical activity level, and high risk of falls were significantly associated with mobility in older patients with osteoporosis.